Temporal expectations guide dynamic prioritization in visual working memory through attenuated alpha oscillations - van Ede, F; Niklaus, M; Nobre, A (Society for Neuroscience, 2017)
While working memory is generally considered a highly dynamic mnemonic store, popular laboratory tasks employed to understand its psychological and neural mechanisms (such as change detection and continuous reproduction) often remain relatively "static", involving the retention of a set number of items throughout a shared delay interval. In the current study, we investigated visual working memory in a more dynamic setting, and assessed: 1) whether internally guided temporal expectations can dynamically and reversibly prioritize individual mnemonic items at specific times at which they are deemed most relevant and 2) the neural substrates that support such dynamic prioritization. Participants encoded two differently colored oriented bars into visual working memory in order to retrieve the orientation of one bar with a precision judgement when subsequently probed. To test for the flexible temporal control to access and retrieve remembered items, we manipulated the probability for each of the two bars to be probed over time, and recorded EEG in healthy human volunteers. Temporal expectations had a profound influence on working memory performance, leading to faster access times as well as more accurate orientation reproductions for items that were probed at expected times. Furthermore, this dynamic prioritization was associated with the temporally specific attenuation of contralateral alpha (8-14 Hz) oscillations that, moreover, predicted working memory access times on a trial-by-trial basis. We conclude that attentional prioritization in working memory can be dynamically steered by internally guided temporal expectations, and is supported by the attenuation of alpha oscillations in task-relevant sensory brain areas. SIGNIFICANCE STATEMENT: In dynamic, everyday-like, environments, flexible goal-directed behavior requires that mental representations that are kept in an active (working memory) store are dynamic too. We investigated working memory in a more dynamical setting than is conventional, and demonstrate that expectations about when mnemonic items are most relevant can dynamically and reversibly prioritize these items in time. Moreover, we uncover a neural substrate of such dynamic prioritization in contralateral visual brain areas and show that this substrate predicts working memory retrieval times on a trial-by-trial basis. This places the experimental study of working memory, and its neuronal underpinnings, in a more dynamic and ecologically valid context, and provides new insights into the neural implementation of attentional prioritization within working memory.